2012
DOI: 10.3141/2297-19
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Transportation Access and Connectivity to Local Economic Outcomes

Abstract: Past research has shown that transportation system improvements can affect economic growth and productivity by changing access to markets and connectivity to intermodal terminals. However, most past research has adopted singular measures of market access and business productivity. This study demonstrates how various transportation projects can have larger or smaller impacts on business concentration and productivity by affecting different aspects of market access in areas with different business mixes. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 16 publications
(6 reference statements)
1
37
0
1
Order By: Relevance
“…The local 40-min and the regional three-hour market sizes in the trade and service industrial sectors were consistently strong factors that affected industry employment concentration, industry labor productivity, and foreign export proportion. However, these factors were less strong in the manufacturing, construction, and industrial utility sectors [10]. Allio (2016) found that if trade costs are low, the firms of each region access almost the same market wherever they settle, and workers consume products indifferently from the two regions.…”
Section: Effects Of Transportation and Mobility Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…The local 40-min and the regional three-hour market sizes in the trade and service industrial sectors were consistently strong factors that affected industry employment concentration, industry labor productivity, and foreign export proportion. However, these factors were less strong in the manufacturing, construction, and industrial utility sectors [10]. Allio (2016) found that if trade costs are low, the firms of each region access almost the same market wherever they settle, and workers consume products indifferently from the two regions.…”
Section: Effects Of Transportation and Mobility Costsmentioning
confidence: 99%
“…Murata and Thisse (2005) examined how low transportation cost facilitated the dispersion of economic activities within a general equilibrium model [9]. Alstadt et al (2012) analyzed the relationship between transportation access, connectivity and local economic outcomes within an industry. The local 40-min and the regional three-hour market sizes in the trade and service industrial sectors were consistently strong factors that affected industry employment concentration, industry labor productivity, and foreign export proportion.…”
Section: Effects Of Transportation and Mobility Costsmentioning
confidence: 99%
“…Higher numbers and darker shading denote a stronger relationship; the three-hour delivery market is shown to be important primarily for manufacturing industries (Alstadt et al, 2012).…”
Section: Emergence Of Evidence On Threshold Factorsmentioning
confidence: 99%
“…For other industries that depend on freight deliveries for incoming delivery of parts and outgoing shipments of finished products, there is a premium value in having access to major seaports, intermodal rail terminals and/or air cargo terminals. For instance, a statistical study of the relative concentration of industries among US counties showed that low travel time to a major airport is a major determinant of business location for two sets of industries: (a) tourism and conference serving sectors (including recreation, lodging and restaurant), and (b) finance, professional and technical services, which have high rates of worker business travel (Alstadt et al, 2012 and …”
Section: Estimating Wider Economic Impacts In Transport Project Priormentioning
confidence: 99%
“…Therefore, the Market Access Module has been designed to evaluate the full impacts of market accessibility with the consideration of both the market accessibility factors and connectivity factors. represents the estimated travel time for trips and reflects the market access benefits in terms of domestic supply chains because it is an appropriate approximation for "same-day deliveries", according to industry surveys (Alstadt et al, 2012). These thresholds are calculated by a gravity model that denotes both the zonal market size (population or employment centered) and zonal access time (functions as a decay factor).…”
Section: Market Access Modulementioning
confidence: 99%